2019
DOI: 10.1093/mnrasl/slz161
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of relative proper motions of wide binaries in Gaia DR2: MOND or multiplicity?

Abstract: We examine the distribution of on-sky relative velocities for wide binaries previously assembled from GAIA DR2 data and focus on the origin of the high velocity tail of apparently unbound systems which may be interpreted as evidence for non-Newtonian gravity in the weak field limit. We argue that this tail is instead explicable in terms of a population of hidden triples, i.e. cases where one of the components of the wide binary is itself a close binary unresolved in the GAIA data. In this case the motion of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Recently, Pittordis & Sutherland (2019) showed that MOND without an EFE is completely ruled out by the observed relative velocity distribution of wide binary stars in the Solar neighbourhood at separations of ≈ 10 kAU. Including the EFE leads to nearly Newtonian behaviour, though the predicted 20% difference is likely detectable in a more thorough analysis (Banik & Zhao 2018c) that must include contamination by undetected close companions (Clarke 2020).…”
Section: Milgrommentioning
confidence: 99%
“…Recently, Pittordis & Sutherland (2019) showed that MOND without an EFE is completely ruled out by the observed relative velocity distribution of wide binary stars in the Solar neighbourhood at separations of ≈ 10 kAU. Including the EFE leads to nearly Newtonian behaviour, though the predicted 20% difference is likely detectable in a more thorough analysis (Banik & Zhao 2018c) that must include contamination by undetected close companions (Clarke 2020).…”
Section: Milgrommentioning
confidence: 99%
“…The more subtle effect with the EFE is still allowed observationally, and should be testable with future data releases and/or further analysis. The main source of contamination is probably hierarchical triples, which should be accounted for statistically (Belokurov et al 2020;Clarke 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the number of wide binaries with unphysically high v depends on r sky similarly to the genuine wide binary population, whose contribution can be estimated from the peak in the v distribution at v ≈ 1. This is very suggestive of the expected close binary contamination (Clarke 2020). In addition, stars in binaries with high v have a poorer Gaia astrometric fit (parallax + proper motion), suggestive of photocentre acceleration induced by an undetected close binary companion (Belokurov et al 2020).…”
Section: Using the Velocity Distributionmentioning
confidence: 60%